Achievement in common entrance examination as a predictor of achievement in junior secondary school business studies (2004)
This study was designed to determine whether or not, the common entrance examination is a true predictor of students' performance in the junior secondary school business studies, using the score of mathematics and english language. It was discovered that while each of mathematics and english language had low positive predictive validity indicies of 0.17 and 0.19 on the performance in junior secondary school business studies, the combined common entrance examination (i.e mathematics and english language scores) predictive value at 0.41 was, however, fairly good as it is about the normal standard average of success in Nigerian examinations. Recommendations are then made that the quality of teacher, of instructional materials and instruction itself be improved upon. It is also suggested that the quality of the textbooks being used in the three subjects at the secondary school level be analysed in order to establish the degree of that quality.